ABCG2 polymorphisms in gout: insights into disease susceptibility and treatment approaches - Cleophas MC; Joosten LA; Stamp LK; Dalbeth N; Woodward OM; Merriman TR (Dove Medical Press, 2017)
MC Cleophas,1,2 LA Joosten,1–3 LK Stamp,4 N Dalbeth,5 OM Woodward,6 Tony R Merriman7 1Department of Internal Medicine, 2Radboud Institute for Molecular Life Sciences, Radboud University Medical Center, Nijmegen, the Netherlands; 3Department of Medical Genetics, Iuliu Haţieganu University of Medicine and Pharmacy, Cluj-Napoca, Romania; 4Department of Medicine, University of Otago Christchurch, Christchurch, 5Department of Medicine, University of Auckland, Auckland, New Zealand; 6Department of Physiology, University of Maryland School of Medicine, Baltimore, MD, USA; 7Department of Biochemistry, University of Otago, Dunedin, New Zealand Abstract: As a result of the association of a common polymorphism (rs2231142, Q141K) in the ATP-binding cassette G2 (ABCG2) transporter with serum urate concentration in a genome-wide association study, it was revealed that ABCG2 is an important uric acid transporter. This review discusses the relevance of ABCG2 polymorphisms in gout, possible etiological mechanisms, and treatment approaches. The 141K ABCG2 urate-increasing variant causes instability in the nucleotide-binding domain, leading to decreased surface expression and function. Trafficking of the protein to the cell membrane is altered, and instead, there is an increased ubiquitin-mediated proteasomal degradation of the variant protein as well as sequestration into aggresomes. In humans, this leads to decreased uric acid excretion through both the kidney and the gut with the potential for a subsequent compensatory increase in renal urinary excretion. Not only does the 141K polymorphism in ABCG2 lead to hyperuricemia through renal overload and renal underexcretion, but emerging evidence indicates that it also increases the risk of acute gout in the presence of hyperuricemia, early onset of gout, tophi formation, and a poor response to allopurinol. In addition, there is some evidence that ABCG2 dysfunction may promote renal dysfunction in chronic kidney disease patients, increase systemic inflammatory responses, and decrease cellular autophagic responses to stress. These results suggest multiple benefits in restoring ABCG2 function. It has been shown that decreased ABCG2 141K surface expression and function can be restored with colchicine and other small molecule correctors. However, caution should be exercised in any application of these approaches given the role of surface ABCG2 in drug resistance. Keywords: ABCG2, BCRP, gout, urate, uric acid, polymorphism, allopurinol